Roles of DgD14 in regulation of shoot branching in chrysanthemum (Dendranthema grandiflorum 'Jinba') - Wen, Chao (Plant physiology and biochemistry : PPB, 2015)
Copyright © 2015 Elsevier Masson SAS. All rights reserved.